Optimization of Information Interaction Protocols in Cooperative Vehicle‐Infrastructure Systems. Issue 2 (1st March 2018) - Zhang, Yuzhuo; Cao, Yuan; Wen, Yinghong; Liang, Liang; Zou, Feng
Abstract : This research investigate the information interaction protocols for Cooperative vehicleinfrastructure systems (CVIS) safety‐related services and optimizes them in three aspects. It puts forward a selfadaptive back‐off algorithm. This algorithm considers retransmission times and network busy degree to choose a suitable contention window. A mathematical analysis model is developed to verify its performance improvement. Finally, different scenario models of Vehicle ad hoc network (VANET) are simulated through the network simulation tool and the influences of different access modes on Quality of Service (QoS) are investigated. The simulation results have verified the improvement of the proposed algorithm is obvious and RTS/CTS access mode can sacrifice slight delay for great improvement of packet lost rate when there are large amount of vehicle nodes.